React quickly - Mardan, Azat; Barklund, Morten (Manning Publications, 2023)
Learn the skills you need to build React applications quickly! This fully revised second edition introduces JSX, functional components, React hooks, event and form handling, and more. In React Quickly, Second Edition you will learn how to: Master React fundamentals Implement best practices and the components of good architecture Build intuitive user interfaces Create dynamic components with JSX Use lightweight functional components in React Make your app interactive with stateful components Utilize React hooks Handle events like button clicks and pass data between components Build your skills with React fast! There's no slow theory and tedious history in React Quickly--you'll dive into React code right from the very first chapter. As you go, you'll explore over 80 useful and practical examples that put React into action. This new second edition has been completely rewritten to cover the latest developments in the React framework. Perfect, whether you're a React beginner or an experienced pro looking to keep their skills up to date. About the Technology React makes it a breeze to build beautiful, reliable web frontends. This amazing JavaScript library has a modular architecture, so you can create, combine, and test components seamlessly. React is perfect for small prototypes, enterprise scale sites, and everything in between. About the Book React Quickly, Second Edition offers a unique approach to learning the React framework. More than 80 concise examples guide you from your first steps through advanced applications. You'll appreciate the up-to-date coverage of functional components, React hooks, and web accessibility, along with interesting projects to practice your new skill. What's Inside Master React fundamentals Best practices of component-based design Create dynamic components with JSX Make your app interactive with stateful components About the Reader For developers comfortable building web applications with JavaScript. About the Authors Morten Barklund is an expert in React, web testing, and accessibility and is the founder of Coding Heaven. Azat Mardan is a seasoned software engineer, startup mentor, and best-selling author. Quotes Simple, clear, and comprehensive with easy-to-follow examples and challenging projects. The perfect balance between theory and practice. - Samer Buna, author of books and courses on React and Node I learned new things even after eight years of React experience. - Swizec Teller, React expert, swizec.com More than a book! Includes a brilliant website with code in a run-time environment. A very accessible learning experience! - Brendan O'Hara, Untapped AI An invaluable resource for beginners and seasoned developers alike. - Ahmad Nassri, Startup Advisor and Investor.
Keywords: JavaScript (Computer program language); Web site development; Web sites -- Design; User interfaces (Computer systems); Application software -- Development; JavaScript (Langage de programmation); Sites Web; Développement; Sites Web; Conception; Interfaces utilisateurs (Informatique); Logiciels d'application; Développement